Konsultasi Teknis Perencanaan Masjid di Kantor Asosiasi Perguruan Tinggi Swasta Indonesia Wilayah IVA Jawa Barat - Muhsin, Ardhiana; Rahadian, Erwin Yuniar; Hendrarto, Tecky (Lentera Karya Edukasi, 2024)
The Association of Indonesian Private Universities Region IVA West Java office needs to build a mosque with an available site next to the main building. This community service activity aims to facilitate this requirement by providing technical discussion to providing architectural drawings. The method used in the design process is a feedback method and the comparative method during the survey stage. The results are not only providing an architectural drawing but also detailed drawings and budget plans in general. In order to provide architectural drawings and detailed drawings, a simple course is also set for vocational high school students